Head and Neck Tuberculosis in Southeastern Region in Turkey, Near the Syrian Border - Tümüklü, Koray; Aytaç, İsmail and Yazıcı, Alper and Aytaç, Sema (European Journal of Therapeutics, 2023)
Objective: The study was conducted to evaluate profiles, demographical data, diagnostic, clinical and treatment approaches in relation to the cases of diagnosed head and neck tuberculosis after the start of the Syrian civil war in 2011. The aim of the study is to share current knowledge on head and neck tuberculosis and to investigate whether there is an epidemiological change with the admission of immigrants after the start of the Syrian civil war. Methods: Demographic data, contact history, relapse, localization, tuberculin test, BCG vaccination and treatment duration are evaluated variables. Two groups were created. The first group was diagnosed with head and neck tuberculosis between 2006 and 2011 before the outbreak of the Syrian civil war, and the second group was diagnosed between 2012 and 2017 after the war in Syria caused hundreds of thousands of Syrian citizens to flee their homes and cross the border into Turkey. Results: Head and neck tuberculosis cases tend to increase after the year of 2012. The number of diagnosed non-Turkish citizens expand after the year of 2012 and reach the highest number in 2017. BCG vaccination status and contact history were found to be the only variables that display statistical significance between the groups. Conclusions: The number of head and neck tuberculosis cases increased after the Syrian war began due to insufficient rates of vaccination among the Syrian population and this population’s overcrowded living environment in Turkey. The burden of these crises affects a region rather than the whole country.